Association of scapular dyskinesis with neck and shoulder function and training period in Brazilian ju-jitsu athletes - Jeong, J. H.; Kim, Y. K. (Medicina, 2023)
Background and Objectives: Neck and shoulder injuries are common in Brazilian ju-jitsu (BJJ) athletes, and scapular dyskinesis (SD) is associated with these injuries. This study aimed to investigate the prevalence of SD in BJJ athletes, their neck and shoulder function and strength, and the BJJ training period.